THE EFFECTS OF ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) DISCLOSURES ON FINANCIAL PERFORMANCE: A THEORITICAL APPROACH - Marginingsih, Ratnawaty; Suparno, Suparno (ANALISIS, 2024)
The implementation of environmental, social and governance (ESG) principles by companies continues to be a topic that is often discussed in international forums. Many negative impacts on the environment that are feared to have a fatal impact around the world make the issue a major concern. This research uses a qualitative method, which aims to provide a preposition of ESG measurement on the company's financial performance. The data collection technique in this study uses a literature survey. The results of this study indicate that the company's commitment to good ESG disclosure is able to produce more transparent financial reporting and corporate performance reporting. This is considered by stakeholders as an important approach in presenting transparent and accountable information. Therefore, the company's ESG disclosure is considered to be able to improve the company's financial performance. Keywords: Environmental, Social, Governance, ESG Disclousures, Financial Performance